2015
DOI: 10.1002/jaba.216
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of positive and negative reinforcement for compliance to treat problem behavior maintained by escape

Abstract: Previous research has shown that problem behavior maintained by escape can be treated using positive reinforcement. In the current study, we directly compared functional (escape) and nonfunctional (edible) reinforcers in the treatment of escape-maintained problem behavior for 5 subjects. In the first treatment, compliance produced a break from instructions. In the second treatment, compliance produced a small edible item. Neither treatment included escape extinction. Results suggested that the delivery of a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
46
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 26 publications
(49 reference statements)
3
46
0
1
Order By: Relevance
“…Delivery of positive reinforcement for compliant behavior may be a viable alternative to escape extinction when treating escape‐maintained problem behavior. Slocum and Vollmer () compared the delivery of nonfunctional edible items to the delivery of escape in reducing escape‐maintained problem behavior and increasing compliance of five children with developmental disabilities. Delivery of edible items was effective in both reducing problem behavior and increasing compliance for all five participants, whereas delivery of escape was effective in reducing problem behavior and increasing compliance for only two of the five participants.…”
mentioning
confidence: 99%
“…Delivery of positive reinforcement for compliant behavior may be a viable alternative to escape extinction when treating escape‐maintained problem behavior. Slocum and Vollmer () compared the delivery of nonfunctional edible items to the delivery of escape in reducing escape‐maintained problem behavior and increasing compliance of five children with developmental disabilities. Delivery of edible items was effective in both reducing problem behavior and increasing compliance for all five participants, whereas delivery of escape was effective in reducing problem behavior and increasing compliance for only two of the five participants.…”
mentioning
confidence: 99%
“…This contingency involved two functional reinforcers: ending the ongoing demands (negative reinforcement) and simultaneously providing contingent access to tangibles or attention (positive reinforcement). In other experiments with participants for whom problem behavior was shown to be sensitive to escape from demands, the use of positive reinforcers (edibles) for compliance was found to be more effective in increasing compliance and decreasing problem behavior than the contingent use of breaks (Lalli et al, 1999;Slocum & Vollmer, 2015). Conducting a preference assessment for break environments may be another way to determine the positive reinforcers to include in treatment protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers manipulating the quality of reinforcement during DRA without extinction for escape‐maintained destructive behavior have done so by providing an “enhanced” escape period in which access to preferred stimuli such as attention, edible items, or leisure activities (i.e., social‐positive reinforcers) are provided during a brief break from instructional demands (i.e., social‐negative reinforcement) contingent upon an alternative behavior (e.g., compliance; Athens & Vollmer, ; Hoch et al, ; Lalli & Casey, ; Piazza et al, ; cf. Adelinis et al, ; Carter, ; DeLeon et al, ; Lalli et al, ; Slocum & Vollmer, ). Specifically, four studies conducted with a total of eight children who engaged in escape‐maintained (Athens & Vollmer, ; Hoch et al, ) or multiply‐controlled (including escape; Lalli & Casey, ; Piazza et al, ) destructive behavior have arranged this manipulation in several ways.…”
mentioning
confidence: 99%
“…For instance, research has shown that manipulating various response and reinforcer dimensions 1 to favor an alternative response over destructive behavior effectively increases the alternative response, even when destructive behavior continues to produce the functional reinforcer (e.g., Athens & Vollmer, 2010;Borrero et al, 2010;Hoch, McComas, Thompson, & Paone, 2002;Horner & Day, 1991;Kunnavatana, Bloom, Samaha, Slocum, & Clay, 2018;Piazza et al, 1999). Specifically, for escape-maintained destructive behavior, researchers have manipulated the magnitude of reinforcement (Athens & Vollmer, 2010), schedule of reinforcement (Lalli & Casey, 1996), delay to reinforcement (Athens & Vollmer, 2010), quality of reinforcement (Adelinis, Piazza, & Goh, 2001;Athens & Vollmer, 2010;Carter, 2010;DeLeon, Neidert, Anders, & Rodriguez-Catter, 2001;Hoch et al, 2002;Lalli & Casey, 1996;Lalli et al, 1999;Piazza et al, 1997;Slocum & Vollmer, 2015), or some combined dimensions of reinforcement (Lalli & Casey, 1996), and examined whether these are effective strategies for treating destructive behavior in the absence of extinction.…”
mentioning
confidence: 99%